2013
DOI: 10.1051/0004-6361/201219430
|View full text |Cite
|
Sign up to set email alerts
|

Eccentricity-pumping in post-AGB stars with circumbinary discs

Abstract: Circumbinary discs are commonly observed around post-asymptotic giant branch (post-AGB) systems and are known to play an important role in their evolution. Several studies have pointed out that a circumbinary disc interacts through resonances with the central binary and leads to angular momentum transfer from the central binary orbit to the disc. This interaction may be responsible for a substantial increase in the binary eccentricity. We investigate whether this disc eccentricity-pumping mechanism can be resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 66 publications
1
112
0
Order By: Relevance
“…In the case of MSPs with the WD companions,it was proposed by Antoniadis (2014) that the disk would form from the material escaping the WD progenitor as it undergoes hydrogen shell flashes prior to entering the WD cooling phase. Dermine et al (2013) and Antoniadis (2014) calculated eccentricity growth driven by tidal coupling of the binary to a non-evolving circumbinary disk with mass~--…”
Section: Introductionmentioning
confidence: 99%
“…In the case of MSPs with the WD companions,it was proposed by Antoniadis (2014) that the disk would form from the material escaping the WD progenitor as it undergoes hydrogen shell flashes prior to entering the WD cooling phase. Dermine et al (2013) and Antoniadis (2014) calculated eccentricity growth driven by tidal coupling of the binary to a non-evolving circumbinary disk with mass~--…”
Section: Introductionmentioning
confidence: 99%
“…Post-asymptotic giant branch (post-AGB) stars also represent a challenge to modellers, as their evolution is thought to involve circumbinary disc-orbit interactions (e.g. Dermine et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Barium stars are binaries where a red giant bears signs of contamination by the nuclear-synthetic products (such as barium) by the former AGB companion (now a WD). By adopting the formalism of Lubow & Artymowicz (1996), Dermine et al (2012) explored the binary-disk interaction regime relevant to barium stars and showed that circumbinary disks may play an important role in pumping the eccentricities of barium stars to the observed values.…”
Section: Introductionmentioning
confidence: 99%